Transportation of Chromium (VI) to Bombyx mori L. from mulberry Plant (Morus alba L.) grown at soil irrigated with Chromium (VI) containing effluents - Ali, Majid; Alamgeer, Muhammad; Qayyum, Mirza Abdul; Zia, Khuram; Ashfaq, Muhammad; Saleem, Muhammad Asad (Journal of Scientific Agriculture, 2021)
The research was conducted to determine Chromium (VI) toxicity in population Bombyx mori. The synthetic wastewater used to irrigate soil to evaluate the impact of pH (4 to 8) at 100 mg/L and initial Chromium (VI) concentrations (25 mg/L to 300 mg/L) at 5 pH in its bioaccumulation in B. mori foodchain. By using atomic absorption spectrophotometer (AAS) analysis the amount of Chromium (VI) determined in soil, mulberry plants, B. mori larvae, silk glands and silkworm feces. The results showed that local cobalt pollution can be indicated by using B. mori as a template as its body length, body weight and the mortality rate were found to be strongly related to Chromium (VI) concentration. Higher the Chromium (VI) amount in mulberry leaves causes more toxicity to B. mori population. At 300 mg/L Cr (VI) concentration and pH 4 there was maximum deposition of Chromium (VI) in soil, mulberry plants, B. mori larvae, faeces and silk glands from the synthetic effluent. The maximum deposition was 123.5±0.03 mg/kg, 89.76±.031 mg/kg, 23.31±0.019 mg/kg, 41.32±0.069 mg/kg and 35.67±0.04 mg/kg observed respectively.